(untitled) (Global Journal of Science Frontier Research, 2012)
The concept of construction and stage-by-stage development of basic model of stationary X-ray induced conductivity for wide-gap semiconductors is proposed. Within the limits of first stage, calculation of spatial distribution of the generated electrons and holes in an ideal crystal which absorbs X-ray flux is carried out and volt-ampere characteristic is calculated.